2019
DOI: 10.48550/arxiv.1905.11528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Training Speed, Accuracy, and Data Utilization Through Loss Function Optimization

Abstract: As the complexity of neural network models has grown, it has become increasingly important to optimize their design automatically through metalearning. Methods for discovering hyperparameters, topologies, and learning rate schedules have lead to significant increases in performance. This paper shows that loss functions can be optimized with metalearning as well, and result in similar improvements. The method, Genetic Loss-function Optimization (GLO), discovers loss functions de novo, and optimizes them for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Genetic Loss Optimization (GLO) [4] provided an initial study into metalearning of loss functions. GLO is based on a two-phase approach that (1) evolves a function structure using a tree representation, and (2) optimizes a structure's coefficients using an evolutionary strategy.…”
Section: A Loss Function Metalearningmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic Loss Optimization (GLO) [4] provided an initial study into metalearning of loss functions. GLO is based on a two-phase approach that (1) evolves a function structure using a tree representation, and (2) optimizes a structure's coefficients using an evolutionary strategy.…”
Section: A Loss Function Metalearningmentioning
confidence: 99%
“…In doing so, it makes it possible to regularize the solutions automatically. Genetic Loss Optimization (GLO) [4] provided an initial implementation of this idea using a combination of genetic programming and evolutionary strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a recent research direction is concerned with loss function meta-learning, with diverse applications in supervised and reinforcement learning [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Although different works utilize different meta-learning techniques and have different goals, it has been shown that loss functions obtained via meta-learning can lead to an improved convergence of the gradient-descent-based optimization.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Meta-learning and Loss Learning Meta-learning, also known as learning to learn, has been applied for a wide variety of purposes as summarized in [12]. Of particular relevance is meta-learning of loss functions, which has been studied for various purposes including providing differentiable surrogates of non-differentiable objectives [14], optimizing efficiency and asymptotic performance of learning [17,2,13,39,7,8], and improving robustness to train/test domain-shift [1,24]. We are particularly interested in learning white-box losses for efficiency and improved task-transferability compared to neural network alternatives [2,13,1,24].…”
Section: Related Workmentioning
confidence: 99%
“…We are particularly interested in learning white-box losses for efficiency and improved task-transferability compared to neural network alternatives [2,13,1,24]. Meta-learning of white-box learner components has been demonstrated for optimizers [38], activation functions [28] and losses for accelerating conventional supervised learning [7,8]. We are the first to demonstrate the value of automatic loss function discovery for general purpose label-noise robust learning.…”
Section: Related Workmentioning
confidence: 99%